Cool-Water Immersion Reduces Post-Exercise Quadriceps Femoris Muscle Perfusion more than Cold-Water Immersion - Mawhinney Chris; Heinonen Ilkka; Low David A; Han Chunlei; Jones Helen; Kalliokoski Kari K; Kirjavainen Anna; Kemppainen Jukka; Di Salvo Valter; Lolli Lorenzo; Cable Tim N; Gregson Warren (United States, 2022)
Purpose: The muscle perfusion response to post-exercise cold water immersion (CWI) is not well understood. We examined the effects of graded post-exercise CWI upon global and regional quadriceps femoris muscle perfusion using positron emission tomography (PET) and [15O]H2O.
Methods: Using a matched-group design, 30 healthy men performed cycle ergometer exercise at 70% V[Combining Dot Above]O2peak to a core body temperature of 38 °C, followed by either 10 min of CWI at 8 °C, 22 °C or seated rest (control). Quadriceps muscle perfusion, thigh and calf cutaneous vascular conductance (CVC), intestinal, muscle, and local skin temperatures, thermal comfort, mean arterial pressure, and heart rate were assessed at pre-, post-exercise and following CWI.
Results: Global quadriceps perfusion was reduced beyond the pre-defined minimal clinically relevant threshold (0.75 mL·100 g·min-1) in 22 °C water versus control (difference [95% confidence interval (CI)]: -2.5 mL·100 g·min-1 [-3.9 to -1.1]). Clinically relevant decreases in muscle perfusion were observed in the rectus femoris (-2.0 mL·100 g·min-1 [-3.0 to -1.0]) and vastus lateralis (VL; -3.5 mL·100 g·min-1 [-4.9 to -2.0]) in 8 °C water, and in the vastus lateralis (-3.3 mL·100 g·min-1 [-4.8 to -1.9]) in 22 °C water versus control. The mean effects for vastus intermedius and vastus medialis perfusion were not clinically relevant. Clinically relevant decreases in thigh and calf CVC were observed in both cooling conditions.
Conclusions: The present findings revealed that less noxious CWI (22 °C) promoted clinically relevant post-exercise decreases in global quadriceps muscle perfusion whereas noxious cooling (8 °C) elicited no effect.